Análise regional do emprego nos estados do nordeste brasileiro - 1995-2003 - Vieira Júnior, Nilson Machado (2006)
The economy of North-East Brazil has changed a lot in the last 30 years. Many studies have analysed the changes that have taken place in this Region, aiming to suggest some development policies for the Region. From a relative isolation and stagnation, North-East Brasil has showed a developing economy, specially in States such as Bahia, Pernambuco and Ceará. This research had as its goal to pinpoint the dynamic sectors of the Region. The basic variable used was the employed labor force throughout the economic sectors and some analysis measures of a sector and regional nature were also employed in this research, along with the shift-share method. The considered employed labor force was from 10 years old and up, and it was divided into economic sectors. The employed labor force considered was those people who were working all or a part of the range time (the week in reference or the reference period of 365 days or less than 4 years). The sectors analysed in this research were: the Agriculture; Industry; Building; Trade and repair; Public Administration, education and health; Household services and Other activities. Some of these sectors turned up to be dynamic and/or showed specific location advantages, which may point to the fact that these sectors can respond positively to a bigger development process, if public policies are taken correctly.